Implementation Of Occupational Safety And Health (K3) In Palm Oil Factory (Case Study: PT X Sumatera Utara) - Debby Octaviani, SP (Citakonsultindo, 2023)
Occupational safety and health in oil palm plantations is not only very important for workers, but occupational safety and health determines the productivity of a job. Occupational health as an aspect or element of health that is closely related to the work environment and work which can directly or indirectly affect work efficiency and productivity. The aim of the research is to explain the Implementation of Occupational Safety and Health at the PT X North Sumatra Palm Oil Factory. The research method used is descriptive analysis to identify an overview of the implementation of occupational safety and health at Palm Oil Factory PT X North Sumatera Those who had a health check were 24 people or (72.7%) respondents and those who did not have a health check were 9 people or (27.3%) respondents. Use of PPE: 28 people used PPE or (84.8%) respondents and 5 people did not use PPE or (15.2%) respondents. There were 31 people who complied with working hours or (93.9%) respondents and 2 people who did not meet the requirements or (6.1%) respondents. The conclusion in this study is that respondents comply with work regulations, use PPE as personal protective equipment, pay more attention to their health, apply work according to K3 regulations by the Palm Oil Factory PT X North Sumatra and is considered very good by the employees themselves.